حاشيتا الملّا خسرو والشّهاب ومباحث علُوم القُرآن فيهما: مقدّمة تفسير البيضاوي أُنموذجا - بلقاضي, هشام; هلال, عبد الحفيظ (جامعة الوادي - University of Eloued, 2021)
يجمع هذا البحث بين دراسة التّراث المخطوط وبين الدّراسات القُرآنية، حيث يهدف هذا المقال إلى استقراء مباحث علوم القرآن من حاشيتين على تفسير البيضاوي: حاشية لا تزال مخطوطة وهي حاشية الملا خسرو، وحاشية مطبوعة وهي حاشية الشّهاب، وهذا مع بيان منهج كلّ واحد منهما في استنباط هذه المباحث، في حدود شرحهما وتحليلهما لمقدمة هذا التّفسير، ثمّ المقارنة بين المنهجين. وقد توصّلت هذه الدّراسة للكشف عن بعض مباحث علوم القرآن ومدى التّرابط فيما بينها على ترتيب ذكر الإمام البيضاوي، وحدّدت نقاط الاتفاق والاختلاف بين الحاشيتين. This research combines the study of manuscript heritage and the Quranic studies, Where this article aims to extrapolate the topics of Quranic sciences from two footnotes on the interpretation of al-Baydawi: A footnote still in manuscript, which is the footnote of Mullah Khosrow, and a printed footnote, which is the footnote of Shihab, With an explanation of the method for each of them in introspection these topics, within the limits of their explanation and their analysis of the introduction of this interpretation, and then a comparison between them. This study found that some of the qur'anic sciences and the link between them, and identified the points of agreement and difference between the two footnotes.
The Footnotes of Mullah Khosrow and Shihab and the Topics of the Qur'an Sciences in them - The Introduction of Interpretation of Al-Baydawi as a Model-
مقال
Keywords: علوم القرآن ; البيضاوي ; حاشية ; الملا خسرو ; الشهاب; The Sciences of The Qur'an; Al-Baydawi; footnote; Mullah Khosrow; Shihab